2018
DOI: 10.1002/sctm.18-0018
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Stem Cells for the Treatment of Surgical Disorders in the Fetus and Neonate

Abstract: SummaryOver the past decade, amniotic fluid‐derived stem cells have emerged as a novel experimental approach aimed at improving outcomes in children with congenital anomalies, including spina bifida, heart defects, and diaphragmatic hernia. Interest in these cells for the treatment of prenatally diagnosed diseases has arisen based on numerous studies demonstrating the relative ease of harvesting an abundant quantity of amniocytes from a small aliquot of fluid, the unique properties of amniocytes themselves, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Our findings highlight the important functional role that AFSC play in promoting cellular regeneration and mitigating NEC-induced damage in intestinal tissue, organoids, and live animals. AFSC can be readily and safely collected, cultured, and expanded 22 , 43 , 44 . Hence, there is great interest in their use for intestinal diseases such as NEC as well as their potential role in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the important functional role that AFSC play in promoting cellular regeneration and mitigating NEC-induced damage in intestinal tissue, organoids, and live animals. AFSC can be readily and safely collected, cultured, and expanded 22 , 43 , 44 . Hence, there is great interest in their use for intestinal diseases such as NEC as well as their potential role in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that cells preferentially home to the exposed spinal cord using a rat fetal MMC model . However, the role of hAFSCs engrafted on the surface of the defective spinal cord remains to be determined . Interestingly, rudimentary skin coverage was macroscopically distinguishable in this study (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…hAFSCs, injected into the amniotic fluid as fetal stem cell therapy, have been shown to preferentially home to the exposed spinal cord using rat fetal MMC models [4,6]. However, the biological basis for hAFSCs-treatment remains to be elucidated [26]. To the best of our knowledge, this is the first study to demonstrate the therapeutic mechanisms of intra-amniotic hAFSCs-injection for the treatment of fetal MMC.…”
Section: Discussionmentioning
confidence: 94%
“…Although neural progenitors derived from human amniotic fluid could potentially be used as an "off-the-shelf" cell therapy product for affected fetuses at the time of repair, autologous use of these patches may also be possible given that amniotic fluid itself could easily be obtained upon prenatal diagnosis, which usually occurs by ultrasound at 18-20 weeks of gestation. 31,32 An autologous approach would have the additional advantage of alleviating concerns regarding the allogeneic immune rejection of donor cells. Currently, the time required for the preparation of our human neural progenitors took 10-12 weeks from amniotic fluid, but more rapid differentiation protocols from pluripotent stem cells have been described.…”
Section: Discussionmentioning
confidence: 99%